PAYMENT TRANSACTIONS’ ENERGY EFFICIENCY - Tetiana Osadcha (Consilium LLC, 2021)
The payment system and infrastructure is a sector that is not given enough attention today in the context of energy efficiency. This sector plays a big role in organizing and ensuring money circulation and funds. It has its value consisting on the one hand of the cost of payment equipment, infrastructure, payment instruments. On other hand, its value consists of the cost of energy for their manufacture and maintenance.